Occupational information as a tool to support labour market institutions, including public employment services - Jolanta KULIŃSKA (Edukacja Ustawiczna Dorosłych)
The article presents the matter of demand for occupational information in labour market institutions, including public employment services. The issue was covered in aspect of demand for occupational information as well as realistic possibilities of usage of occupational information bases. It discusses the need and availibility of occupational information from various sources and emphasises the importance of continuously developing, supplementing and updating these occupational information sources. The essence of this work is utilisation of standardised model for creating occupational information, that will answer consumer needs, keep up with dynamic changes in the world of labour and will be an opportunity for extending the possibility of unre-stricted usage of high quality occupational information bases.